Composição centesimal e de fitoquímicos em jambolão (Syzygium cumini) - Barcia, Milene Teixeira (2009)
The jambolanum is a tree originating from India and Indonesia, belonging to the family of Mirtaceas. The tree bears fruit during January to May in several Brazilian states. The fruit are small, purpleand involves a single core. The taste of jambolanum not stand out so much because the astringency of the fruit. The consumption of tropical fruit is growing in the last years due to the appeal of nutritional and therapeutic effects. These fruits contain different phytochemicals, many of these exhibit antioxidant properties, especially the tocopherols, carotenoids and phenolic compounds, because its property of reacting with free radicals. Among the phenolic compounds there are the flavonoids that chemically, include anthocyanins and flavonols. Practically do not know the chemical composition of jambolanum because; therefore, the knowledge of some of its components is important to predict the feasibility of their use as in natura foods and as raw material for the production of other products. This study aimed to evaluate the chemical composition of the fruits of jambolanum collected from three cities in the southern state of RS. The experiment consists of three trees in three different cities of the southern of RS(Santa Vitória do Palmar, Pelotas and Capão of Leão), and its was analyzed for chemical and phytochemical compositiont.By the results it was found that the jambolanum fruit shows the chemical composition similar to other fruits, presenting low amount of ash, proteins, pectin and fiber. The moistureand sugar content and pH is characteristic of citrus fruit; however, the fruit showed higher soluble solids content. The Jambolanum fruit presents low tocopherols and ascorbic acid content, but it showed a high content of tannins and phenol compounds.